The impact of saffron (Crocus sativus) supplementation on visual function in patients with dry age-related macular degeneration - Abbas Riazi; Yunes Panahi; Ali A. Alishiri; Mohammad A. Hosseini; Ali A. Karimi Zarchi; Amirhossein Sahebkar (Italian Journal of Medicine, 2016)
The aim was to evaluate the impact of saffron supplementation on visual function in patients with dry age-related macular degeneration (ARMD). Fifty-four participants, 23 males and 31 females, with dry ARMD were assigned to one of the following two groups. The treatment group (n=29) consumed 50 mg saffron daily during a 3-month period, while 25 subjects served as the control group. Visual acuity, contrast sensitivity, and retinal thickness were measured at the beginning and at the end of the study. Quality of life was evaluated using the Melbourne low vision index before and after treatment. Significant increases in visual acuity and contrast sensitivity were found in the saffron group but not in the control group. Changes in macular thickness were not statistically different between the two groups. Short-term consumption of saffron may slow down the progression of disease and improve visual function, especially contrast sensitivity, in patients with dry ARMD.